Effect of Storage Time to Ferulic Acid Content in Extracted Banana Stem Waste Juice - N., Zainol; N., Masngut; S. N., Ismail (Informatics Publishing Limited, 2017)
Objectives: The present of Ferulic Acid (FA) in plants attract the attention of many researchers, especially in food, pharmaceutical and cosmetic industries. Banana Stem Waste (BSW) was generated from banana plantation. Methods/Statistical Analysis: In this study, FA was extracted from BSW by using sugarcane press machine. Extracted BSW juice (EBJ) was characterized based on the compositions of total phenolic and glucose. The effect of storage time of EBJ was studied. Design Expert software was used for the experimental design. One factor design was applied for the factorial analysis. Findings: The FA was analyzed by using High Performance Liquid Chromatography (HPLC) and FA yield ranging from 0.1101 mg/g to 0.2274 mg/g. The analysis of the results showed that storing EBJ at room temperature increased the ferulic acid yield however the ferulic acid decreased when the storage time exceed 24 hr. Application/Improvements: Effect of storage time to extracted ferulic acid concentration will be understood which in turn may be beneficial for the industrial purpose.